Coloration and functionalization of organic cotton fabric using Chinese fringe leaf extraction: A greener approach - Hossain, Md Shazzat; Ullah, Mohammad; Mia, Rony; Assiri, Mohammed Ail; Zhou, Yahui; Saeed, Haroon A.M.; Mahmud, Sakil (Elsevier B.V., 2025)
This study investigates the innovative use of natural dyes derived from Chinese fringe (Chionanthus retusus) leaves for dyeing organic cotton fabric (OCF), marking the first application of this approach. The natural dyes were extracted from the Chinese fringe leaves and applied on OCF using different mordanting conditions for coloration and functionalization of the fabric. Spectroscopic analyses, including UV−visible (UV−vis) spectroscopy and Fourier transform infrared spectroscopy (FTIR), confirmed the presence of flavonoid compounds as the key bio−colorants in the dye solution. Optimal dyeing conditions were established with a 10 % Al2(SO4)3 mordant, resulting in dyed OCF exhibiting a significant color strength (K/S) of 5.90 and excellent fastness including rubbing, washing and light. Comprehensive characterization techniques, such as optical microscopy, scanning electron microscopy (SEM), elemental mapping, and FTIR, validated the successful dyeing process which ensure the bonding between natural dyes and fabrics in the presence of mordant. Thermal analyses indicated that the OCF retained acceptable properties of DTG at 357 °C after−dyeing. The dyed OCF also demonstrated superior UV protection, with an Ultraviolet Protection Factor (UPF) value of 59.19 ± 1.82, and minimal UV transmission in the UV−A and UV−B regions. Despite a slight reduction in air permeability compared to the undyed OCF, the dyed OCF maintained good breathability. This research highlights the potential of Chinese fringe leaf extracts for eco−friendly coloration and functional enhancement of OCF. The findings have significant implications for the textile industry, offering a path towards more environmentally responsible manufacturing practices without compromising on performance or aesthetics.